Effect of transdermal estradiol therapy on bone mineral density of amenorrheic female athletes - Nose-Ogura, S.; Yoshino, O.; Kanatani, M.; Dohi, M.; Tabei, K.; Harada, M.; Hiraike, O.; Kawahara, T.; Osuga, Y.; Fujii, T. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Background: The effects of transdermal estradiol treatment (HT) in amenorrheic athletes (AA) with low body weight (BW) and low bone mineral density (BMD) are unknown. Purpose: To investigate whether HT increases BMD in AA with low BW and to compare the results with levels in AA who have recovered spontaneous menstruation (SM). Methods: Female athletes (n = 151) were recruited at the Japan Institute of Sports Sciences and the University of Tokyo. All participants were divided into four groups: an AA group (untreated group) (n = 36), a HT group (n = 55), a SM group (n = 21), and an eumenorrheic athletes (EA) group (n = 39). Height, body weight, blood tests, and dual-energy X-ray absorptiometry were measured at baseline and after 12 months. The HT group was treated daily for 12 months with transdermal estrogen therapy. In addition, participants received oral progestin for 7 days once every 3 months. Results: After 12 months, BMD in the AA group was significantly lower than at baseline; however, BMD in the other three groups was significantly higher than at baseline. The ratio of the change in BMD values before and after 12 months was -1.6 ± 3.2% for the AA group, 5.3 ± 8.7% for the HT group, 11.1 ± 8.9% for the SM group, and 2.3 ± 5.7% for the EA group. The rate of change in BMD values in the SM group was greater than that in the HT group. Conclusion: HT increased BMD in AA with low BW, and the increase in those with SM was greater than that in those treated with HT.